PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE SHOPEE DALAM PERSPEKTIF EKONOMI ISLAM - Tilawati, Rahma; Kusnadi, iwan; Marina, Marina (Cross-Border Journal of Business Management, 2024)
This research is motivated by the creation of online buying and selling transactions called online shopping or another term is e-commerce. Shopee is e-commerce no. 1 Indonesia which applies the marketing mix marketing concept which is a combination of four variables, namely product, price, place, and promotion where the concept is one of the marketing activities that will determine the company's success in pursuing profit or mashlahah. This study aims to determine the effect of the marketing mix (product, price, place, promotion) partially or simultaneously on Purchase Decisions at Shopee E-commerce in an Islamic Economic Perspective. The subjects of this study were students of the Islamic Economics and Business Faculty, Sultan Muhammad Syafiuddin Sambas Islamic Institute with a total sample of 67 students. The object of this research is product (product), price (price), place (place), promotion (promotion) Against Purchase Decisions on E-commerce Shopee. The method in this research is quantitative. The sampling technique used is purposive sampling. The analytical method used in this research includes validity test, reliability test, classical assumption test and hypothesis testing through multiple linear regression analysis. The results showed that partially the product variable had no effect on purchasing decisions, it could be seen from the value of tcount < ttable (1.148 < 1.66980) with a significance of 0.225 > 0.05, while the other variables, namely price, place and promotion partially had a positive and significant effect. to purchasing decisions. Simultaneously the marketing mix (product, price, place, promotion) has a positive and significant effect on purchasing decisions with the results of the F test where the value of Fcount > Ftable (14.706 > 2.52) with a significance of 0.000 < 0.05.